Dermatologists Should Encourage and Resume Photoprotection in Patients with Photodermatoses and Melasma Following the COVID-19 Pandemic - Chaisuwannarak K; Rujitharanawong C; Chaiyabutr C; Wongpraprarut C; Silpa-archa N (Clinical, Cosmetic and Investigational Dermatology, 2023)
Kornkanok Chaisuwannarak, Chuda Rujitharanawong, Chayada Chaiyabutr, Chanisada Wongpraprarut, Narumol Silpa-archa Department of Dermatology, Faculty of Medicine Siriraj Hospital, Mahidol University, Bangkok, ThailandCorrespondence: Narumol Silpa-archa, Department of Dermatology, Faculty of Medicine Siriraj Hospital, Mahidol University, Bangkok, Thailand, Email doctornarumol@gmail.comBackground: The COVID-19 pandemic may alter individuals’ perspectives and behaviors regarding sun exposure and photoprotection. Presently, there is a paucity of information about how the pandemic influences photoprotection in photodermatoses and melasma.Objective: To compare the photoprotection attitudes and behaviors of individuals with photodermatoses and melasma with those of a control group (other dermatologic patients) before and during the COVID-19 pandemic.Methods: A questionnaire-based, cross-sectional study was conducted among Thai patients with photodermatoses, melasma, and other dermatological conditions between August 2021 and November 2022. Each of the three groups consisted of 35 patients.Results: Among the 105 patients, 81.9% were female, and the mean age was 45.83 years. Over 80% of individuals who used surgical masks daily for 4 to 8 hours believed that these masks provided skin protection from the sun. The duration of sun exposure and the frequency of photoprotection practices decreased significantly in all groups during the COVID-19 pandemic compared to the pre-pandemic period. Sunscreen was the most prevalent form of photoprotection, but its usage declined considerably during the pandemic. Upon physical examination, the photodermatoses and control groups exhibited unchanged skin conditions, while the patients with melasma demonstrated improved skin conditions during the pandemic.Conclusion: Owing to increased indoor activities and the perception that face masks could block sunlight, the COVID-19 pandemic led to notable reductions in sun exposure and photoprotective practices. Despite the absence of photodermatoses exacerbation and the observed improvements in patients with melasma, consistent and effective photoprotection must continue to be promoted.Keywords: COVID-19 pandemic, melasma, photodermatoses, photoprotection